Knowledge, Attitudes and Practices Regarding Dengue Fever among Adult Population of Kurram Khyber Pakhtunkhwa - Muhammad Asif Ali Shah, Zian Asif, Aiman Fatima, Neelam Raheel, Mirza Zeeshan Sikandar, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Fever caused by dengue is one of the most important potential viral re-emerging diseases, especially in sub-tropics and tropics, infecting around fifty million people all over the world. Dengue virus (DENV) is spread through mosquito bite and is a member of the genus Flavivirus and has four serotypes (DENV-1, 2, 3, and 4), all of which are capable of inducing hemorrhagic dengue fever and dengue shock syndrome. There are several fates of infection caused by dengue virus ranging from asymptomatic infection to subclinical infection and clinical presentation that may be undistinguishable fever or dengue hemorrhagic fever. Active surveillance, effective reporting and case management can reduce the threat of dengue. Methodology: The current KAP survey of dengue assess the knowledge, attitudes and preventive practices of the general public which through statistical analysis showed the mismatch between the knowledge and practices towards dengue disease. Results: The results of current study have identified that the participants in the survey had negative knowledge, attitudes and practices toward dengue. The KAP parameters decreased along with decreased educational status, exposure to telecommunication facilities, awareness about the signs/symptoms, severity and fatality of disease and about the mosquito related preventive measures. Conclusion: It was concluded that in the current KAP survey the Knowledge, Attitudes and Preventive practices towards dengue fever among all the participants was different and this difference mainly due to backward education system, low socio-economic status.